Research of Types of Learned Helplessness of Future Specialists in Foreign Philology - Yuliia Bokhonkova; Svitlana Tsymbal; Nataliia Yaremenko; Nataliia Buhaiova (Insight: the psychological dimensions of society, 2023)
The purpose is to conduct empirical research and theoretically substantiate the types of learned helplessness of future specialists in foreign philology in the context of educational and professional training. The respondents of the empirical research are graduates of the final years of study: students of the fourth year – Bachelor’s degree seekers and students of the second year – Master’s degree seekers, the total number of 432 individuals (M=24.23; SD=±3.08; Me=24; Mo=22). The respondents were majoring in a single or double specialty. Methods. Valid and reliable psychodiagnostic tools that have been adapted and tested were used: “Attributional Style Questionnaire” (ASQ) (Peterson et al., 1982); Ehlers’ questionnaire “Motivation for Achieving Success and Avoiding Failures” (MASAF) (Elers, 2002); the questionnaire “Level of subjective control” (LSC) (Bazhin et al., 1984); Zung Self-Rating Depression Scale (SDS) (Zung, 1965). Results. The provided descriptive statistics confirms that there are no statistically significant differences between the obtained empirical data and the results of similar measurements. Eighteen statistically significant correlations (р<.050; р<.010) of attributive style parameters with independent variables were found: motivation for achieving success, motivation for avoiding failures, level of depression, level of subjective control in educational and professional activities, areas of success, areas of failure. It was established that the level of depression (LD) has the strongest correlations with the attributional style scales: permanence of the bad (R=.189; p<.010), pervasiveness of the bad (R=.221; p<.010) and personalization of the bad (R =.185; p<.010), which gave grounds to consider depressive states as the most dangerous in the formation of learned helplessness. Cluster analysis using the k-means method revealed four types of learned helplessness of future specialists in foreign philology: “Depressive learned helplessness” (cluster 1, n=31; 13.36%), “Avoidant learned helplessness” (cluster 2, n=75; 32.33%), “Optimistic learned helplessness” (cluster 3, n=68; 29.31%), “Uncontrolled learned helplessness” (cluster 4, n=58; 25.00%). Discussion and сonclusions. It was substantiated that the types of learned helplessness are personal formations that were manifested in a high level of depression, the dominance of pessimistic parameters of the attributional style of behavior, a high level of motivation for avoiding failures, a low level of motivation for achieving success, and low/lack of subjective control of the events of educational and professional activities. The appropriateness of implementing the obtained results in the educational and scientific processes of training future specialists in the socionomic profile was empirically clarified and theoretically substantiated.